Searching for diagnoses and subgroups: a suggestion for criteria - Steinert, Tilman (Frontiers in Psychiatry, 2024)
New subgroups of psychiatric disorders are often claimed. In contrast, classification systems have repeatedly had to abandon established subgroups such as paranoid vs. disorganised and catatonic schizophrenia due to lack of empirical evidence. Four criteria are proposed that should be met to claim valid subgroups: 1. distinct distribution of the defining characteristic between groups; 2. significant differences in variables other than those defining the subgroups cross-sectionally and longitudinally; 3. long-term stability; 4. significant differences between groups in aetiology, pathophysiology, and evidence-based therapy. In contrast to examples from somatic medicine, such as type 1 and type 2 diabetes, few psychiatric disorders meet these requirements."Maybe there is a subgroup..." is a popular conclusion in research articles with inconsistent results.Psychiatrists, as well as physicians in general, like to classify patients into diagnostic categories and suggest further diagnostic subgroups. While the DSM-1 contained 106 diagnostic classifications, the DSM-5 contains 374. The idea that psychiatric classification should refer not only to observed actual symptoms but also to "underlying" disease entities was first developed by the German psychiatrist Karl Kahlbaum (1828-1899) in his textbook (1). Two decades later, Emil Kraepelin (1856Kraepelin ( -1926) )